Asynchronous Telepractice and Ethical Conduct. - Cohn, Ellen R.; Cason, Jana (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: This invited article reflects upon elements of ethical behavior during the conduct of asynchronous telepractice. Method: First, telepractice is defined, followed by the typically understood definitions of synchronous telepractice, asynchronous telepractice, and hybrid telepractice (in-person plus synchronous and/or asynchronous telepractice approaches). In this in-depth examination of ethical intent and behavior, the point is made that synchronous and asynchronous telepractice can be simultaneously or sequentially linked for the same clinician--client interaction. The article then presents key elements of the Code of Ethics of the American Speech-Language-Hearing Association, along with historical underlying ethical principles. It includes practical vignettes of model ethical conduct and conduct that violates at least one principle of ethics. Conclusions: It is important to not embrace a false or superficial dichotomy between synchronous and asynchronous telepractice when considering ethical behavior. In fact, the same ethical principles apply to both.